2014
DOI: 10.1136/neurintsurg-2014-011449
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of intracranial aneurysms treated by flow diverter: comparison of three-dimensional time-of-flight MR angiography (3D-TOF-MRA) and contrast-enhanced MR angiography (CE-MRA) sequences with digital subtraction angiography as the gold standard

Abstract: At 3 T, CE-MRA is superior to 3D-TOF-MRA for the evaluation of aneurysm occlusion and parent artery patency after flow diversion treatment. However, intraluminal evaluation remains difficult with MRA regardless of the sequence used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 24 publications
2
41
0
1
Order By: Relevance
“…High-attenuation platinum alloy coils causes marked beam hardening and streak artifact on CT and CTA, which typically obscure not only the aneurysm but also the adjacent parent and branch vessels as well as the surrounding brain parenchyma. Platinum alloy coils create relatively little distortion of the local magnetic field and, therefore, cause much less dramatic disruption of the MRI and MRA signal intensity (3,22,23,25,26).…”
Section: █ Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High-attenuation platinum alloy coils causes marked beam hardening and streak artifact on CT and CTA, which typically obscure not only the aneurysm but also the adjacent parent and branch vessels as well as the surrounding brain parenchyma. Platinum alloy coils create relatively little distortion of the local magnetic field and, therefore, cause much less dramatic disruption of the MRI and MRA signal intensity (3,22,23,25,26).…”
Section: █ Resultsmentioning
confidence: 99%
“…Until recently, the gold standard technique has been catheter-based DSA that is usually performed at either 3 In follow-up of intracranial aneurysms treated with endovascular coil occlusion, two different MRA techniques (3D-TOF-MRA and CE-MRA) are discussed (18). Most have reported the superiority of CE-MRA (3,12). CE-MRA has been shown to be as accurate as conventional catheter-based cerebral angiography.…”
Section: █ Discussionmentioning
confidence: 99%
“…В недавно проведенном исследовании у пациентов, пролечен-ных с использованием стентов-диверторов кровото-ка, J. Attali и соавт. [36] обнаружили, что при силе магнитного поля 3 Тл CE-МРА позволяла обнаружить рецидив аневризмы с чувствительностью 83% и специ-фичностью 100% по сравнению с TOF-МРА с чувст-вительностью 50% и специфичностью 100% соответст-венно. Тем не менее оба метода были неэффективны в отношении оценки просвета питающего сосуда.…”
Section: другие устройства для эмболизацииunclassified
“…In a recent study on patients treated with flow diverter stents, Attali et al 36 found that at 3T, aneurysm recurrence can be detected using CE-MRA with a sensitivity of 83% and a specificity of 100% when compared with TOF-MRA with sensitivity and specificity values of 50% In clinical practice, imaging follow-up of patients with stents always requires at least 1 DSA examination, often performed between 6 and 12 months after the embolization, when stopping 1 antiplatelet therapeutic is considered. An MRA is simultaneously performed for further comparison in follow-up imaging.…”
Section: Other Embolization Devicesmentioning
confidence: 99%
“…Hulley et al 3 suggests the use of the FINER criteria in designing research questions, which should be f easible, i nteresting, n ovel, e thical, and r elevant. Attali et al ,4 in a paper on follow-up imaging after flow diverter treatment, provide a concise illustration of an effective introduction.…”
Section: Introductionmentioning
confidence: 99%